2019
DOI: 10.1158/1541-7786.mcr-18-0731
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of EGFR and IGF1R in the TNFAIP8 Knockdown Non–Small Cell Lung Cancer Cells

Abstract: Aberrant regulation of EGFR is common in non-small cell lung carcinomas (NSCLC), and tumor resistance to targeted therapies has been attributed to emergence of other cooccurring oncogenic events, parallel bypass receptor tyrosine kinase pathways including IGF1R, and TNFadriven adaptive response via NF-kB. TNFAIP8, TNFa-inducible protein 8, is an NF-kB-activated prosurvival and oncogenic molecule. TNFAIP8 expression protects NF-kB-null cells from TNFa-induced cell death by inhibiting caspase-8 activity. Here, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…EGFR is one of the most common growth factors implicated in numerous malignancies. A previous study showed that TNFAIP8-knockdown enhances the expression of sorted nexin 1 and upregulates the endosomal/lysosomal transport pathway, resulting in decreased EGFR expression, decreased EGF-induced phosphorylated extracellular signal-regulated kinase expression, reduced cell migration and increased sensitivity to EGFR mutation-selective tyrosine kinase inhibitors (68). In TNFAIP8-knockdown cells, the expression of IGF-1 binding protein 3 (IGFBP3) was shown to be increased, leading to a decrease in the IGF-1-induced expression of pIGF1R and p-Akt, decreased cell migration, and enhanced sensitivity to PI3K and Akt inhibitors, suggesting that targeting TNFAIP8 can inhibit adaptive responses and provided a rational strategy for the management of aggressive NSCLC (68).…”
Section: Current Studies Of Tnfaip8 In Tumoursmentioning
confidence: 99%
“…EGFR is one of the most common growth factors implicated in numerous malignancies. A previous study showed that TNFAIP8-knockdown enhances the expression of sorted nexin 1 and upregulates the endosomal/lysosomal transport pathway, resulting in decreased EGFR expression, decreased EGF-induced phosphorylated extracellular signal-regulated kinase expression, reduced cell migration and increased sensitivity to EGFR mutation-selective tyrosine kinase inhibitors (68). In TNFAIP8-knockdown cells, the expression of IGF-1 binding protein 3 (IGFBP3) was shown to be increased, leading to a decrease in the IGF-1-induced expression of pIGF1R and p-Akt, decreased cell migration, and enhanced sensitivity to PI3K and Akt inhibitors, suggesting that targeting TNFAIP8 can inhibit adaptive responses and provided a rational strategy for the management of aggressive NSCLC (68).…”
Section: Current Studies Of Tnfaip8 In Tumoursmentioning
confidence: 99%
“…26 Day et al found that using IGFBP3 siRNA to treat NSCLC cells with TNFAIP8 knockdown can upregulate pAKT levels and promote cell proliferation. 27 By blocking the IGF1 signal cascade, it was possible to confirm to a certain degree that overexpression of IGFBP3 can induce apoptosis in NSCLC cells in vitro and enhance cellular response to cisplatin. 28 In lung adenocarcinoma and hepatocellular carcinoma, testis-specific protein Y-linked 1 (TSPY1) can directly bind to the promoter of IGFBP3 to inhibit its expression.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that TIPE is overexpressed in various tumors and that its overexpression is associated with clinical parameters and metastasis. In non-small-cell lung cancer (NSCLC), the expression of TIPE is downregulated via a decrease in EGFR levels and an increase in SNX (a key regulator of EGFR transporters) levels, which further inhibits ECL- and IGF-1-stimulated NSCLC cell migration ( 5 ). In gastric cancer patients, increased TIPE expression in tumor tissue is related to lymph node metastasis, tumor-node-metastasis (TNM) stage, and poor prognosis ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-induced protein-8 (TNFAIP8/TIPE; also called SCC-S2, MDC-3.13, GG2-1, and NDED) was the first identified protein in the TIPE family and is closely associated with tumors and inflammation ( 4 ). As an antiapoptotic and carcinogenic molecule, TIPE promotes the growth, proliferation and migration of cancer cells ( 5 ). The activation of TNF-α and NF-κB in the inflammatory environment can induce TIPE expression ( 6 ).…”
Section: Introductionmentioning
confidence: 99%